2021
DOI: 10.3390/ijerph18094718
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Tolerance Trend in Extended-Spectrum β-Lactamase Encoding Strains Recovered from Food Samples

Abstract: This study evaluates bacteriological profiles in ready-to-eat (RTE) foods and assesses antibiotic resistance, extended-spectrum β-lactamase (ESBL) production by gram-negative bacteria, and heavy metal tolerance. In total, 436 retail food samples were collected and cultured. The isolates were screened for ESBL production and molecular detection of ESBL-encoding genes. Furthermore, all isolates were evaluated for heavy metal tolerance. From 352 culture-positive samples, 406 g-negative bacteria were identified. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
1
5
3
Order By: Relevance
“…These organisms carry plasmid-mediated resistance genes and cause community-acquired human infections. However, in this study, no significant difference in prevalence was observed between these bacterial isolates, consistent with the results of previous studies [ 21 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These organisms carry plasmid-mediated resistance genes and cause community-acquired human infections. However, in this study, no significant difference in prevalence was observed between these bacterial isolates, consistent with the results of previous studies [ 21 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study describes the presence of multiple AMR in foodborne bacterial isolates with biofilm formation potential, in combination with heavy metal tolerance. Previous studies have indicated that dairy products made from raw milk could be the main source of antibiotic-resistant bacteria that threaten food safety [ 21 , 36 ]. This problem is pervasive in developing countries because of poor food handling methods and hygiene standards, inadequate food safety rules and regulatory systems, and unsatisfactory education of food handlers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being frequently found in bottled mineral water and tap water, P. aeruginosa has also been tested positive in ready-to-eat vegetables ( Naze et al, 2010 ; Pelegrin et al, 2021 ; Ruiz-Roldán et al, 2021 ). Studies found the ready-to-eat vegetables that were a potential-although rare-vector for colistin- and carbapenem-resistant P. aeruginosa , the contamination rate of P. aeruginosa has reached 17.5% or 34% ( Cai et al, 2015 ; Hölzel et al, 2018 ; Kapeleka et al, 2020 ; Junaid et al, 2021 ). That is to say, P. aeruginosa is a major contaminant of fresh vegetables, which might be a source of infection for susceptible persons within the community ( Rahman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method will lead to wrong judgment in actual inspection: one case is that some strains of P. aeruginosa do not produce this pigment, which leads to missed inspection. Another situation is that P. fluorescens produces the same pigment as P. aeruginosa , which makes it impossible to distinguish and cause false positive ( Schroth et al, 2018 ; Junaid et al, 2021 ). For a long time, scientists have been committed to establishing a rapid and sensitive method for the detection of P. aeruginosa , but each method has its advantages and disadvantages ( Tang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%